Beneficial effects of rolipram in a quinolinic acid model of striatal excitotoxicity - Zena DeMarch; Carmela Giampà; Stefano Patassini; Alessandro Martorana; Giorgio Bernardi; Francesca Romana Fusco (Neurobiology of Disease, 2007)
Activity of c-AMP responsive element-binding protein (CREB) is decreased in Huntington’s disease (HD). Such decrease was also described by our group in the quinolinic acid lesion model of striatal excitotoxicity. The phosphodiesterase type IV inhibitor rolipram increases CREB phosphorylation. Such drug has a protective effect in global ischaemia and embolism in rats. In this study, we sought to determine whether rolipram displays a neuroprotective effect in our rat model of HD. Animals were surgically administered QA and subsequently treated with rolipram daily up to 2 and 8 weeks respectively. After these time points, rats were sacrificed and immunohistochemical studies were performed in the striata. In the rolipram-treated animals, striatal lesion size was about 62% smaller that in the vehicle-treated ones at 2 weeks time point. Moreover, the surviving cell number was several times higher in the rolipram-treated animals than in the vehicle group at both time points. Rolipram also showed to be effective in increasing significantly the levels of activated CREB in the striatal spiny neurons, which accounts mostly for its beneficial effect in our rodent model of excitotoxicity. Our findings show that rolipram could be considered as a valid therapeutic approach for HD.